2022
DOI: 10.1097/shk.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography-based body-surface thermal inhomogeneity monitoring to assess the severity of hypoperfusion in critically ill patients

Abstract: Background: Uneven body-surface thermal distribution is a manifestation of hypoperfusion and can be quantified by infrared thermography. Our aim was to investigate whether body-surface thermal inhomogeneity could accurately evaluate the severity of patients at risk of hypoperfusion. Methods: This was a prospective cohort study in which infrared thermography images were taken from unilateral legs of critically ill patients at high risk of hypoperfusion in a cardiac surgical intensive care unit. For each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains ( 11 , 12 , 18 , 20 , 24 , 25 , 27 , 30 , 36 , 39 ). One scored high-risk ratings across all domains ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of studies with a low-risk rating for concerns around the applicability of their findings in the patient selection, index test and reference standard domains were 73, 57 and 77%, respectively. Ten studies scored low risk ratings across all domains ( 11 , 12 , 18 , 20 , 24 , 25 , 27 , 30 , 36 , 39 ). One scored high-risk ratings across all domains ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of authors identified their studies as exploratory or assessing feasibility ( n = 16) ( 11 , 12 , 14–16 , 19 , 21 , 22 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 ). Few were described as validation or diagnostic accuracy studies ( n = 8) ( 13 , 17 , 18 , 20 , 24 , 33 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group have established a prospective cohort gathering infrared images of the legs of critically ill patients at high risk of hypoperfusion, collecting routine hypoperfusion parameters and following up on their prognosis. Based on these data, we defined parameters reflecting thermal inhomogeneity of body surface (e.g., low temperature area rate [LTAR] and standard deviation [SD]) using traditional mathematical methods and found that these parameters varied among patients with different severity of hypoperfusion and could be used to predict the risk of mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%